Arabic Language Development in Boarding Schools at the Industry Era 4.0: Potentials and Challenges - Noza Aflisia; Hendriyanto Hendriyanto; Andewi Suhartini (Alsuna: Journal of Arabic and English Language, 2022)
Purpose - This study aims to analyze and present the potential for Arabic language development through education in Boarding Schools and the challenges faced in the current era of the Industrial Revolution 4.0. Design/methodology/approach – The technique of analyzing research data is carried out through several stages, namely: processing and preparing data, classifying data, reading all the data that has been obtained, analyzing the special potential of Boarding Schools for Arabic language development, and identifying challenges faced by Islamic boarding schools in developing Arabic, as well as clarifying and drawing conclusions on the results of the analysis obtained. Findings/results – The results showed that the potential of Boarding Schools in developing Arabic at least consisted of academic and professional potential, technology, religiosity, politics, and economics. In developing the existing potential, Islamic boarding schools are faced with the challenge of making students master communicative Arabic and technology. Originality/value - This research further describes in more detail the potential and challenges of developing Arabic in Islamic boarding schools. so that the understanding and knowledge gained are deeper and more comprehensive. Considering the Arabic language reaps many problems and challenges and makes Arabic an interesting study to study at this time. Paper type – Conceptual paper